O prevodih Hlapca Jerneja in njegove pravice - Priestly, Tom (Slavistična revija, 2001)
This article discusses two extant English translations of Ivan Cankar's Hlapec Jernej in njegova pravica (by Adamič and by Jeras-Guinot & Grant) and three Russian translations (by Šerement'ev, by Ohrimenko, and by Urban), with reference to their treatment of the crucial contrast in the story between" the "divine" and "the earthly". First, Orhimenko's version is considered: it is not a translation of Cankar's original, but of Adamič's translation; it omits nearly all the religious elements in the original, but is inconsistent in this respect. The religious elements of the original are grouped in five categories for analyses, and the five texts are analyzed; far-reaching differences among the five translations are demonstrated. The two previous assesments of Adamič's "adaptation" of this story are reviewed. It is suggested that the difference among the Russian versions correspond to the degree of anti-religious Soviet propaganda current at tthe times of their publication.
Keywords: Cankar, Ivan, 1876-1918; Cankar, Ivan: Hlapec Jernej in njegova pravica; prevodi; Slovene literature; slovenska književnost